Scenario analysis to determine possible, plausible futures for the New Zealand dairy industry. Issue 3 (3rd July 2017) - Shadbolt, Nicola; Apparao, Dhananjay; Hunter, Simon; Bicknell, Kathryn; Dooley, Anne
ABSTRACT: New Zealand accounts for just 3% of global milk production, yet it is the largest global trader of milk across borders. In contrast to other milk-producing countries, less than 5% of New Zealand milk is consumed within the country so producers must be constantly aware of changing global forces with respect to supply of, and demand for, their products. This study involved a multitude of stakeholders and used scenario analysis as a tool to arrive at four future scenarios for dairy in New Zealand. It was demonstrated that by using this approach, it is possible to arrive at a robust description of possible, plausible, futures which can guide the design of future farm systems, facilitate the understanding and recognition of factors that might shape the future of agribusiness and provide a rich source of material that can be used to inform and possibly frame and test strategy and policy.